1997
DOI: 10.1523/jneurosci.17-06-02143.1997
|View full text |Cite
|
Sign up to set email alerts
|

Interconnected Parallel Circuits between Rat Nucleus Accumbens and Thalamus Revealed by Retrograde Transynaptic Transport of Pseudorabies Virus

Abstract: One of the primary outputs of the nucleus accumbens is directed to the mediodorsal thalamic nucleus (MD) via its projections to the ventral pallidum (VP), with the core and shell regions of the accumbens projecting to the lateral and medial aspects of the VP, respectively. In this study, the multisynaptic organization of nucleus accumbens projections was assessed using intracerebral injections of an attenuated strain of pseudorabies virus, a neurotropic ␣ herpesvirus that replicates in synaptically linked neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
143
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 168 publications
(149 citation statements)
references
References 118 publications
(155 reference statements)
6
143
0
Order By: Relevance
“…A major source of glutamatergic projection to the NAc is the PVT (Berendse and Groenewegen, 1990;O'Donnell et al, 1997;Van der Werf et al, 2002;Smith et al, 2004;Vertes and Hoover, 2008). Our current results reveal that synaptic transmission in PVT neurons projecting to the NAc is essential for acquisition of cocaine self-administration but not for incubation of cocaine craving after cocaine withdrawal.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…A major source of glutamatergic projection to the NAc is the PVT (Berendse and Groenewegen, 1990;O'Donnell et al, 1997;Van der Werf et al, 2002;Smith et al, 2004;Vertes and Hoover, 2008). Our current results reveal that synaptic transmission in PVT neurons projecting to the NAc is essential for acquisition of cocaine self-administration but not for incubation of cocaine craving after cocaine withdrawal.…”
Section: Discussionmentioning
confidence: 67%
“…One of the less-examined major projections is from the paraventricular nucleus of the thalamus (PVT), which, as a subnucleus of the thalamus, lies on the midline just ventral to the third ventricle (Van der Werf et al, 2002;Smith et al, 2004). The PVT projection often converges with other excitatory inputs or midbrain-originated dopaminergic terminals onto the same NAc medium spiny neurons (MSNs; Berendse and Groenewegen, 1990;O'Donnell et al, 1997;Otake and Nakamura, 1998;Pinto et al, 2003;Vertes and Hoover, 2008). This anatomical setup allows the PVT-to-NAc projection to either activate NAc MSNs directly or interact with other inputs.…”
Section: Introductionmentioning
confidence: 99%
“…The serotonergic axons of the nucleus accumbens stimulate the thalamic reticular nucleus, and serotonin excites the GABAergic neurons of the thalamic reticular nucleus (34). An interconnected circuit also exists between the thalamic reticular nucleus and the nucleus accumbens, with the nucleus accumbens subsequently influencing inhibitory gating on the thalamocortical relay (35). The input of the thalamic reticular nucleus inhibits the neurons of the medial geniculate nucleus (36).…”
Section: Discussionmentioning
confidence: 99%
“…This virus retrogradely infects synaptically connected neurons in the CNS after injection into various peripheral organs (Card and Enquist, 1994;Loewy, 1995) and, as found more recently, after direct injection in the CNS (Kaufman et al, 1996;O'Donnell et al, 1997). The latter studies, however, revealed problems specific to CNS injection; in particular, it has not been possible to determine the extent of the injection site histologically.…”
Section: Abstract: Pain Pathways; Amygdala; Superficial Dorsal Horn;mentioning
confidence: 99%